Effects of Compression Stockings on the Risk of Obstructive Sleep Apnea (OSA) in Hemodialysis Patients - Astilia, Astilia; Bandiara, Ria; Kosasih, Cecep Eli; Ibrahim, Kusman (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2020)
Background: Obstruction Sleep Apnea (OSA) in hemodialysis patients is a sleep disorder that involves stopping or decreasing air flow to breathe during sleep due to excess fluid in the leg. Compression Stockings (CS) with 30-40 mmHg are high pressure elastic stockings that are assumed to reduce foot fluid accumulation during the day and to prevent overnight fluid shifting to the neck.Purpose: This study aimed to determine the effects of 30-40 mmHg CS on the risk of OSA in hemodialysis patients.Method: This research used a quasi-experimental pre-posttest with control group design. A purposive sampling was applied to recruit as many as 68 hemodialysis patients. The risk score of OSA was measured using STOP Bang questionnaire. High pressure CS were given for one week to the intervention group with two OSA measurements on the 4th and 7th days. The data then were analyzed using the Post Hoc Wilcoxon test and the Mann Whitney test.Results: There was a significant difference between the risk score for OSA before and after the use of 30-40 mmHg Compression Stocking in the intervention group on day 4 (p=0.000) and day 7 (p=0.000) compared to the control group.Conclusion: High pressure CS decreased the risk of OSA in hemodialysis patients by avoiding fluid retention in the legs, thus preventing fluid shifting to the neck. CS should be recommended as an alternative to prevent the risk of OSA in hemodialysis patients.